2012
DOI: 10.1016/j.jinorgbio.2012.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Metal-binding domains and the metal selectivity of the vanadium(IV)-binding protein VBP-129 in blood plasma

Abstract: Ascidians are well known to accumulate extremely high levels of vanadium in their blood cells. Several key proteins related to vanadium accumulation and physiological function have been isolated from vanadium-rich ascidians. Of these, vanadium(IV)-binding protein-129 (VBP-129) is a unique protein that has been identified from the blood plasma of an ascidian Ascidia sydneiensis samea, but its metal binding domains are not known. In this study, several deletion and point mutants of VBP-129 were generated, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The protein–vanadium complex was synthesized according to the method suggested by Ueki et al . with some modification.…”
Section: Methodsmentioning
confidence: 99%
“…The protein–vanadium complex was synthesized according to the method suggested by Ueki et al . with some modification.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the natural VBP from ascidians were attracted widespread attention (Ueki et al, 2003). It has been reported that the highest concentration of vanadium in Ascidia gemmata (350 mM) was approximate 1 × 10 7 times higher than that in natural seawater (Fukui et al, 2003;Ueki et al, 2012). In the previous study, the VBP from sea squirt Halocynthia roretzi, which is a traditional tonic food in Korea and Japan, exhibited strong inhibitory activity against a-glucosidase and adipocyte differentiation (Gunasinghe & Kim, 2018;Liu et al, 2015).…”
mentioning
confidence: 99%